Swot Analysis In Determining Marketing Strategy (Case Study At Afina Jaya Malang Souvenir Shop) - Siti Maisaroh; Siswahyudianto (Cita konsultindo, 2023)
This study aims to determine what marketing strategies can be applied to increase sales of Toko Afina Jaya Malang through SWOT analysis. This study uses a type of qualitative research. Primary data was obtained through interviews and observations to deepen the data obtained. Secondary data were obtained through a literature study from Toko Afina Jaya and the author's documentation. The data that has been collected is then analyzed using the IFAS EFAS matrix and the SWOT matrix. The results of measurements on the IFAS matrix for strength have a total score of 2.00 and weaknesses have a total score of 1.91. So it can be concluded that the strength is greater than the weakness. Whereas on the EFAS matrix, opportunities have a total score of 1.71, and threats have a total score of 1.63. So it can be concluded that Afina Jaya's opportunities are greater than the threats it has. Then, based on the results of the SWOT analysis diagram, Afina Jaya is in the first square position, namely supporting an aggressive growth policy (growth-oriented strategy). So that the appropriate strategy is SO, which is to continue to improve good service to consumers, increase inventory stock during major holidays, continue to provide affordable prices without reducing quality, continue to support business development, and increase distributor relations.